The written language process of students with learning difficulties in remote teaching times (Research, Society and Development, 2022)
The present research approaches writing and rewriting as a tool for the development of higher psychological functions of students with learning difficulties and it aims to comprehend the writing and rewriting as mediators in the development of higher psychological functions in students with teaching difficulties of students from Elementary School. We applied the writing and rewriting of text as instruments, based on a review guided by the teacher. To meet the goal of the study, we carried out a qualitative research, through a case study, with intervention workshops based on the assumptions of the Historical-Cultural Theory. We conducted these interventions with five students from the 3rd and 4th grades from the Elementary School who had a diagnosis on learning difficulties. From the textual genre Fable, we carried out textual productions reviewed by the teacher and rewritten by the students, during the months from June to August 2020, remotely due to the pandemic. We verified, after analyzing the collected data, that the writing and rewriting procedures of text contributed to the mobilization of the required attention, memory and language of students with learning difficulties, but as we applied it remotely, we did not obtain the expected result because of lack of the physical presence of the teacher as a mediator at the time of the fulfillment from the activities resulted in losses for the students who were helped at home by their own families.